Impact of compressive force on macrophages and cementoblasts and the possible interrelation with orthodontically induced inflammatory root resorption - Wang, Yao; Justus Liebig University Giessen (My University, 2025)
This study analyzes the impacts of orthodontic compressive force on both innate immune responses and cementum homeostasis (Figure 22). In macrophages, compressive force induces chromatin rearrangement, nuclear shrinkage, and polarization. Two distinct mechanotransduction pathways were identified: 1. Histone H3 hyperacetylation: This mediates M2 polarization during the late stage of the immune response. 2. Lamin A/C downregulation: Orthodontic compressive force transiently reduces lamin A/C levels, compromising the nuclear envelope and increasing nuclear permeability to YAP1. This facilitates enhanced force-induced cytokine expression and proliferative inhibition. Concurrently, it reduces force-induced IRF4 expression, DNA damage, and phagocytosis enhancement, likely due to LINC complex disruption. These opposing effects of lamin A/C deficiency jointly regulate cellular behavior under compressive force. Furthermore, cementoblasts respond directly to compressive force but do not respond to macrophage-conditioned medium, suggesting that excessive orthodontic force, rather than macrophage activation, is the primary driver of OIIRR. Mechanistically, Piezo1 activation under force mediates enhanced hypoxia and suppressed mineralization in a Ca2+-independent manner. Lastly, LMCD1 and POSTN were identified as downstream mediators of Piezo1, representing potential therapeutic targets for OIIRR.
Keywords: ddc:610